2019
DOI: 10.1186/s13063-018-3119-0
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition Tolerance And REspiratory Support (ENTARES) Study in preterm infants: study protocol for a randomized controlled trial

Abstract: BackgroundRespiratory distress syndrome (RDS) and feeding intolerance are common conditions in preterm infants and among the major causes of neonatal mortality and morbidity.For many years, preterm infants with RDS have been treated with mechanical ventilation, increasing risks of acute lung injury and bronchopulmonary dysplasia.In recent years non-invasive ventilation techniques have been developed. Showing similar efficacy and risk of bronchopulmonary dysplasia, nasal continuous positive airway pressure (NCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…Despite some authors highlighting the possible key role of dysbiosis in the pathogenesis of ROP and non-communicable chronic diseases, this evidence remains somewhat speculative, and other factors, such as respiratory support or diet, need to be further investigated [74,75,76].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…Despite some authors highlighting the possible key role of dysbiosis in the pathogenesis of ROP and non-communicable chronic diseases, this evidence remains somewhat speculative, and other factors, such as respiratory support or diet, need to be further investigated [74,75,76].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…Other studies [ 26 , 27 ] have reported, in contrast, an association between increased GRs and NEC, but they were retrospective and had many confounding factors which limit their value. Thus, GRs alone are an unreliable marker of NEC, while in association with other suspicious clinical signs [ 16 ] they can contribute to a rational management of enteral nutrition and to the planning of any diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was determined by abdomen pathological physical examination, regurgitations/vomits, GRs with volume ≥ 100% of previous feed and/or altered (i.e. : hematic, fecaloid), mucous or bloody stools, and onset of apnea/bradycardia [ 16 ]. The severity of these conditions was graded as minor and major criteria of feeding intolerance and were used for deciding the interruption of enteral feeding: the occurrence of one to two minor criteria suggested no change in the volume of feed, while the occurrence of three minor criteria or one major criterion suggested discontinuation of enteral feeding [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Feeding intolerance is a frequent complication in preterm infants receiving noninvasive respiratory support. It is unclear whether nHFT has the same deleterious effect of nCPAP on feeding tolerance in preterm infants 26 . Evidence from one RCT showed that preterm infants treated with nHFT achieved full oral feeding at the same rate as infants treated with nCPAP 27 .…”
Section: Discussionmentioning
confidence: 99%